Low-dose decitabine-intensified modified conditioning regimen alleviates aGVHD in AML/MDS patients treated with allogeneic hematopoietic stem cell transplantation - Zhu, Jinye; Wang, Qingya; Ren, Hanyun; Dong, Yujun; Yin, Yue; Wang, Qian; Liang, Zeyin; Liu, Wei; Wang, Qingyun; Wang, Bingjie; Li, Yuan (Frontiers in Immunology, 2023)
Background: The widespread adoption of Allogeneic Hematopoietic Stem Cell Transplantation (Allo-HSCT) has significantly improved the survival rates of patients with hematological malignancies.However, Graft-Versus-Host Disease (GVHD) remains a formidable complication, threatening patient prognosis. Recent research has indicated that decitabine (DAC), known for its hypomethylating properties may also exhibit immune-regulatory capabilities and a potential for reducing GVHD incidence and enhancing survival.Methods: We retrospectively reviewed data from AML/MDS patients who underwent Allo-HSCT at our center from January 2010 to January 2023. From a total of 251 patients with complete data, we employed propensity score matching (PSM) to create 100 matched pairs (200 patients) for 2 This is a provisional file, not the final typeset article comprehensive trial analysis. Patients receiving low-dose DAC-containing regimen were matched with those who did not receive DAC.Results: Patients in the DAC group exhibited a significantly lower incidence of grade II-IV acute GVHD (aGVHD) compared to non-DAC group (21% vs. 38%, P=0.013). Univariable and multivariable logistic regression analysis demonstrated DAC intervention as a protective factor against grade II-IV aGVHD (P=0.017, OR=0.47, 95% CI 0.23-0.81; P=0.018, OR=0.46, 95% CI 0.24-0.87).Multivariate competing risk regression further supported administration of decitabine as a protective factor against grade II-IV aGVHD (P=0.038, SHR=0.53, 95%CI 0.29-0.97). There was no significant difference between both groups concerning chronic GVHD, infection, disease relapse, overall survival, disease-free survival and GVHD free, relapse free survival. In MRD negative or intermediate risk subgroup, the grade II-IV aGVHD ameliorating effect of DAC was confirmed as well.Conclusions: Low-dose DAC-intensified modified conditioning regimen could improve prognosis in AML/MDS Patients treated with allogeneic hematopoietic stem cell transplantation.